Complete androgen insensitivity syndrome in two sisters: Physical and psychological results after different approach of neovagina formation - Anastasia Vatopoulou; Theofilos Kanavos; Fani Gkrozou; Effrosyni Birbas; Orestis Tsonis; Chara Skentou; Minas Paschopoulos (Elsevier, 2023)
Complete androgen insensitivity syndrome (CAIS) occurs in XY individuals due to androgen receptor dysfunction and presents with female phenotype and primary amenorrhea. Patients are typically raised and identify themselves as female and the absence of an upper vagina results in psychological and sexual problems. The cases of two sisters with CAIS that were managed differently regarding the neovagina formation are presented. Non-surgical neovagina formation results in sufficient vaginal depth and satisfying sexual life and may be preferred over the operation. Our findings highlight that the interaction of CAIS patients with each other and the continuous psychological and physical support by the medical team contribute significantly to the outcome.